A Marginal Stability Paradigm for Shear‐Induced Diapycnal Turbulent Mixing in the Ocean. Issue 2 (14th January 2022) - Mashayek, A.; Baker, L. E.; Cael, B. B.; Caulfield, C. P.
Abstract: Turbulent mixing induced by breaking internal waves is key to the ocean circulation and global tracer budgets. While the classic marginal shear instability of Richardson number ∼1/4 has been considered as potentially relevant to turbulent wave breaking, its relevance to flows that are not steady parallel shear flows has been suspect. We show that shear instability is indeed relevant in the ocean interior and propose a new marginal stability paradigm that relates the stability criterion based on Richardson number to one based on the ratio of Ozmidov and Thorpe turbulence scales. The new paradigm applies to both ocean interior and boundary layer flows. This allows for accurate quantification of the transition from downwelling to upwelling zones in a recently emerged paradigm of ocean circulation. Our results help climate models more accurately calculate the mixing‐driven deep ocean circulation and fluxes of tracers in the ocean interior. Plain Language Summary: Internal waves induced by tides, winds, currents, eddies, and other processes abound in the ocean interior. Widespread breaking of internal waves, similar to surface coastal waves, plays an important role in sustaining the ocean circulation by upwelling the densest waters that form in polar regions and sink to the ocean abyss as well as in transport and storage of heat, carbon, and nutrients. In this work, we show how a well‐understood classic hydrodynamic instability facilitates such wave breaking on the global scale in a fashion that keeps the turbulent mixing induced by breaking waves optimally efficient. Key Points: Shear instability is the final stage of turbulence breakdown as nonlinear interactions of various processes downscale energy to small scales The classic stability criteria based on Richardson number is not sufficient and Reynolds number needs to be considered in tandem A generalized criteria based on ratio of overturn scale to turbulent scale seems to umbrella both Richardson and Reynolds number criteria